2013
DOI: 10.1155/2013/452329
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Strategy ofLabeobarbus batesii(Boulenger, 1903) (Teleostei: Cyprinidae) in the Mbô Floodplain Rivers of Cameroon

Abstract: Aspects of the reproductive strategy of African carp,Labeobarbus batesii, were investigated from May 2008 to October 2009 in the Mbô Floodplain of Cameroon. Samples were collected monthly from artisanal fishermen. The total length and total body mass of each specimen were measured to the nearest mm and 0.01 g, respectively. Sex was determined by macroscopic examination of the gonads after dissection. The sex ratio was female skewed (overall sex ratio: 1 : 1.42). Females reach sexual maturity at a larger size (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…e breeding season of C. nigrodigitatus coincides with the continuous rainy season, which lasts approximately six months and is characterized by a single spawning season in June as reported elsewhere [11,12,24,25]. International Journal of Zoology e reproduction of C. nigrodigitatus is of the asynchronous type as reported elsewhere [11,12], thus making this species a partial or heterochronous breeder, or fish with multiple spawning or split-spawning. e peak breeding period observed between April and June is similar to that recorded by Ekamen [26] and Offem et al [27] in the Cross River in Nigeria in the same species and by Dia [28] and Dossou [7], respectively, in Ivory Coast and in Benin.…”
Section: Breeding Periodmentioning
confidence: 59%
See 2 more Smart Citations
“…e breeding season of C. nigrodigitatus coincides with the continuous rainy season, which lasts approximately six months and is characterized by a single spawning season in June as reported elsewhere [11,12,24,25]. International Journal of Zoology e reproduction of C. nigrodigitatus is of the asynchronous type as reported elsewhere [11,12], thus making this species a partial or heterochronous breeder, or fish with multiple spawning or split-spawning. e peak breeding period observed between April and June is similar to that recorded by Ekamen [26] and Offem et al [27] in the Cross River in Nigeria in the same species and by Dia [28] and Dossou [7], respectively, in Ivory Coast and in Benin.…”
Section: Breeding Periodmentioning
confidence: 59%
“…A positive correlation has been recorded between the gonadosomatic and the hepatosomatic indices, whereas logically these two weight indices vary in opposite directions. Indeed, the fish would draw the reserves of the liver (in particular, the vitellogenin in the females) to manufacture the sexual products as discussed elsewhere [11,12,32]. It should probably be due to the fact that some females emit their eggs in a split way; and the partially emptied ovaries do not return to complete rest but continue the vitellogenesis of oocytes that will be emitted later.…”
Section: Breeding Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the abundant diversity of Cameroon's fishery resources associated with its geoclimatic diversity, the main species raised are imported (Cyprinus carpio, Oreochromis niloticus, Clarias gariepinus, Heterobranchus longifilis, Heterotis niloticus) [5]. The introduction of non-native species can lead to invasions, a problem that remains the second leading cause of biodiversity loss worldwide [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In Cameroon, the best knowledge of endogenous species for domestication is likely to overcome to limit the constraints of adaptation, pledge of the Millennium prescription for the preservation and enhancement of endogenous biodiversity [6,8,7]. According to Tiogué et al [9], endogenous species found in several agro-ecological zones of Cameroon may be important potential candidates for aquaculture.…”
Section: Introductionmentioning
confidence: 99%